THE HISTORY OF TRANSPORT SYSTEM IN THE UK (Промышленный Транспорт Казахстан, 2025)
The purpose of this article is to summarise the major changes affecting transport systemsin the UK over the last 100 years.The first section identifies significant points of change in the main transport modes. Thesecond section addresses the principal factors accounting for these changes. The third sectionexamines the consequences for the economy, social inequality and the environment. The articlealso refers to the overarching trends and issues for consideration. From the historical analysisfive issues were identified as relevant to the future of transport in the UK.Interactivity: while transport analysis and policy is often directed towards single modes(e.g. road, rail), it is clear that developments in some modes have been closely connected withthose in others. Most journeys in the past were multi-modal. Mobility revolution: evidence pointsto a transformation in personal mobility in the later twentieth century, driven by consumerdemand. Transformation has occurred in scale and scope in automobility, air travel and, morerecently, rail travel.Overload: one of the results of the surge in the circulation of people and goods has beenoverloaded transport systems: congested roads, crowded trains and airports. Sustainability:since the oil crisis of 1973 the sustainability of transport has been a major issue, encompassingrenewable resources, carbon emissions and pollution. Government has worked towards greatersustainability but it remains a major challenge.Alternatives: transport systems have been relatively stable over the last century, qualifyingthe idea of an imminent breakthrough to a new phase of transport. History suggests that changeis as much a matter of recycling the old as introducing the new. The past thus remains animportant resource for transport alternatives in the future.